Partial discharge detection device using ultrasonic sensor on medium voltage XLPE cable - I. F Radzi; N H Nik; A. Mohd Ariffin; M. S. Abd Rahman; M. R Rahman; M. R Ahmad; A. S Salleh; Ir. Ts. Dr. Norhidayu Rameli (Institute of Advanced Engineering and Science, 2024)
There are many methods that have been studied by earlier researchers in order to detect the acoustic properties of Partial Discharge (PD) emitted by PD sources. One of the methods known as ultrasonic sensing on medium voltage Cross-Linked Polyethylene (XLPE) cable was adopted to detect partial discharges on commercial applications, usually by using Acoustic Emission (AE) sensors. This paper presents the processes of designing a PD sensor to detect the acoustic properties of the partial discharges on medium voltage XLPE cable. This PD sensor method works by detecting the partial discharges occurred at the joint of the cable which can act as an early warning device to help minimize the repair and maintenance costs of degrading cable. Result of the experiment shows the complete design of the prototype device, the device after fabrication and the functionality of the device. This design of the prototype can be beneficial for future uses in designing cost efficient and smaller sized PD detection devices. By positioning the sensor in horizontal position directly to the source of PD on the cable, the sensor will be able to detect acoustic properties of PD, by picking up the frequencies beyond 40 kHz. By varying the voltage applied values, a design of experiment (DOE) is carried out accordingly. Result of the experiment shows that the prototype device is functioning as expected, and hence this finding will be very useful to the consumers of power industries as the sensor device can serve as an alternative device to the commercialized PD sensing devices which are bulky and expensive.